ADAPTATION OF INFORMATION AND COMMUNICATION TECHNOLOGY OF PIKIRAN RAKYAT NEWSPAPER IN THE DIGITAL ERA - Solihin, Olih; Sovianti, Rina; Adi, Fajar (Universitas Komputer Indonesia, 2023)
The rapid development of information and communication technology is currently pushing the mass media industry, especially newspapers, to make adjustments. The development of this technology has changed human habits in accessing information from the mass media. One adjustment to the development of digital technology is through media convergence. If one wants to survive in the digital era, convergence is absolutely necessary. This study aims to identify and analyze the strategies undertaken by the management of the Pikiran Rakyat newspaper to maintain its existence in the digital era. Data collection was carried out through in-depth interviews with the management of the Pikiran Rakyat newspaper, as well as a literature review of previous research on the same topic. The analysis results show that the Pikiran Rakyat newspaper applies the multimedia, multichannel, and multiplatform (3M) strategy. According to the management, implementing this strategy is the answer to the dynamic changes in people's perspectives on obtaining information. Hopefully, this research can serve as a reference for future media studies and information and communication technology researchers, and provide useful insights for the mass media industry as it adjusts to the current digital era.